Quantifying electron-transfer in liquid-solid contact electrification and the formation of electric double-layer - Lin, Shiquan (Nat Commun, 2020)
Contact electrification (CE) has been known for more than 2600 years but the nature of charge carriers and their transfer mechanisms still remain poorly understood, especially for the cases of liquid–solid CE. Here, we study the CE between liquids and solids and investigate the decay of CE charges on the solid surfaces after liquid–solid CE at different thermal conditions. The contribution of electron transfer is distinguished from that of ion transfer on the charged surfaces by using the theory of electron thermionic emission. Our study shows that there are both electron transfer and ion transfer in the liquid–solid CE. We reveal that solutes in the solution, pH value of the solution and the hydrophilicity of the solid affect the ratio of electron transfers to ion transfers. Further, we propose a two-step model of electron or/and ion transfer and demonstrate the formation of electric double-layer in liquid–solid CE.